127k views
3 votes
Solve the system by substitution.

Y=-x^2+x-1
y=-x-1

A. (3,-4), (-1,0)
B. (-1,0), (2,-3)
C. (4,-5), (1,-1)
D. (0,-1), (2,-3)

User Lycon
by
5.5k points

2 Answers

6 votes

Answer:

D

Explanation:

User Erp
by
5.0k points
3 votes

Answer:

D

Explanation:

y = -x^2 + x - 1

y = -x -1

-x-1 = -x^2 + x -1

x^2 -2x = 0

x( x-2) = 0

x1= 0 , x2 = 2

y(0) = 0-1 = -1

y(2) = -2-1 = -3

(0, -1) & (2, -3)

User JosefAssad
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.